P–231 Transnational oocyte donation program between Italy and Spain based on transport of vitrified oocytes: a five-years experience. (6th August 2021) - Volpes, A; Gullo, S; Modica, M; Scaglione, P; Marino, A; Quintero, L; Allegra, A
Abstract: Study question: What is the clinical efficacy of an oocyte donation program based on the transportation of vitrified oocytes between two countries? Summary answer: The transnational oocyte donation program is efficient, safe and comparable to other strategies (transport of frozen sperm and embryos). What is known already: Egg donation represents a valid treatment strategy for women who have exhausted their ovarian function and it has considerably increased in the last years. In Italy, egg donation is allowed after the judgment of the Constitutional Court n. 162 in 2014 but no reimbursement for the donors is provided. For this reason, the number of voluntary donors is irrelevant. Therefore, the great majority of egg donation cycles is carried out by using imported cryopreserved oocytes from foreign countries. However, recent evidence has questioned the overall efficacy of this strategy in comparison with the shipment of frozen sperm and vitrified embryos. Study design, size, duration: A retrospective cohort study was conducted between July 2015-December 2020 at two private IVF clinics. 264 couples were treated (mean maternal age: 43.1± 4.6 years, range: 26–51; mean donor age: 24 ±3 years, range: 20–33) with vitrified oocytes shipped from a single Spanish egg bank (IMER, Valencia) to the receiving reproductive clinic in Italy (ANDROS Clinic, Palermo). All the oocytes for each batch were thawed. Participants/materials, setting, methods: The primary outcome of this study was the cumulative clinical pregnancy rate (CPR) among the completed cycles for each batch of oocytes. Those cycles in which a clinical pregnancy was obtained, or all embryos derived by a single batch of oocytes had been transferred or no embryo was produced were defined as completed. In addition to main analyses, sensitivity analysis was performed to examine how the number of inseminated oocytes may affect CPR. Main results and the role of chance: 2, 367 oocytes in 355 batches were sent from Spain to Italy. 2, 209 oocytes in 334 batches for 264 patients were thawed with a survival rate of 82.4% (1, 821/2, 209). The mean number of oocytes received per patient was 6.6 ± 1.0. The fertilization rate was 72.1% (1, 312/1, 821). 499 embryos were transferred (38.0%), 335 at the cleavage stage (67.1%) and 164 at the blastocyst stage (32.9%); 197 supernumerary embryos were vitrified (15.0%), 18 at the cleavage stage (9.1%) and 179 at the blastocyst stage (90.9%). 616 embryos were not viable (47.0%). No more than two embryos were transferred for each embryo transfer (ET). The completed cycles were 307 out of 334 (91.9%). The CPR per completed cycles was 46.6% (143/307) and 54.2% per patient (143/264). Clinical pregnancy rate per fresh ET in completed cycles with supernumerary cryopreserved embryos was significantly higher compared with that of the completed cycles without surplus embryos (56/101 versus 68/193, p = 0.001). Logistic regression revealed that the number of inseminated oocytes was positively associated with CPR in a significant manner (B = 0.220, p = 0.007; OR = 1.25, 95%CI=1.06–1.47). The multiple pregnancy rate was 15.4% (1 triplet and 21 twin pregnancies). The miscarriage rate was 22.4% (32/143). Limitations, reasons for caution: The retrospective design of the study needs to be confirmed in larger and multicenter prospective studies comparing the strategy of vitrified donated oocytes and fresh ET with the policy of fresh donated oocyte and frozen/thawed ET. Wider implications of the findings: The transnational oocyte donation program with vitrified oocytes is associated with good success rates. The number of inseminated oocytes represents a crucial factor for increasing the CPR, improving the embryo selection for fresh ET and giving more chances of pregnancy with the transfer of surplus vitrified embryos. Trial registration number: Not applicable